The effect of viral marketing,promotions and flash sales on the purchase intention online shopping z generation in marketplace tiktok shop - Mustikasari; Suhardi M. Anwar; Andi Rizkiyah Hasbi (Institute of Computer Science (IOCS), 2023)
This study aims to examine the effect of viral marketing, promotion and flash sale variables on purchase intentions in the Tiktok shop marketplace. The analytical method used is quantitative analysis by conducting a survey using the Google form which has been distributed to 104 respondents with generation z consumers who use the TikTok shop application as the object of this study. testing in this study used the help of the SPSS 23 analysis tool. The results of the study showed that the influence of the viral marketing variable (X1) did not have a significant effect on purchase intention (Y) because the significant value was 0.069> 0.05 and tcount 1.838 <ttable 1.984. while the promotion variable (X2) and flash sale variable (X3) have a significant effect on purchase intention (Y), this is evidenced by the promotion variable (X2) obtaining a significant value of 0.000 <0.05 and tcount 6.364>t table 1.984 and the flash sale variable (X3) obtained a significant value of 0.002 <0.05 and tcount 3.253> ttable 1.984. but the variable viral marketing (X1), promotion (X2) and flash sale (X3) have a positive and significant effect simultaneously on the variable purchase intention (Y).